DAPF: Delay‐aware packet forwarding for driving safety and efficiency in vehicular networks. Issue 9 (1st June 2020) - Shahwani, Hamayoun; Mugabarigira, Bien Aime; Shen, Yiwen; Jeong, Jaehoon (Paul); Shin, Jitae
Abstract : This study proposes an effective delay‐aware packet forwarding (DAPF) for driving safety and efficiency in vehicular networks. Vehicular ad hoc networks have been an emerging technology for vehicular communication for the last few decades, but still, it has many challenging issues such as on‐time dissemination of message at an emergency situation (e.g. accident and obstacle) to the vehicles having the same route to their destinations. This on‐time dissemination can prevent further collision of vehicles and road traffic congestion. In this study, the authors propose an effective way of selecting the processing position of a message among a cluster head, road‐side unit (RSU), and vehicular cloud, on the basis of total delivery time and cost. They further show that this effective selection and on‐time dissemination helps the upcoming vehicles to select an appropriate route to their destinations. Through simulation results, it is shown that their DAPF outperforms other schemes in terms of packet delivery time.